Enhancing Students' Metacognitive Knowledge through Problem-Based Learning Integrated with Cognitive Conflict Approach: A Study in Newtonian Physics Education (Jurnal Penelitian dan Pengkajian Ilmu Pendidikan: e-Saintika, 2024)
This study investigates the effectiveness of a Problem-Based Learning (PBL) model integrated with cognitive conflict strategies in improving students’ metacognitive knowledge in physics education. Conducted in an Indonesian senior high school, the study involved three classes implementing different instructional models: PBL with cognitive conflict, PBL alone, and expository teaching. Using a pretest-posttest design, students’ declarative, procedural, and conditional metacognitive knowledge was assessed. Descriptive and inferential analyses revealed that all instructional models produced significant learning gains, with the PBL + cognitive conflict model showing the most notable improvements, especially in conditional knowledge (n-gain = 0.72; Cohen’s d = 1.20). Although ANOVA results were statistically non-significant, effect size analysis confirmed substantial educational impact. The findings highlight the dual role of cognitive conflict and metacognitive scaffolding in fostering self-regulated learning and conceptual understanding. This study supports the integration of metacognitive strategies into inquiry-based instructional models and underscores the cultural compatibility of PBL in Indonesian educational settings.